Performance analysis of IP traffic over a WDM ring network in the presence of crosstalk - Dambul, Katrina D.; Abbou, F. M.; Chuah, Hean Teik (The Institute of Electronics, Information and Communication Engineers, 2005)
This paper evaluates the performance of IP traffic over WDM ring network in the presence of linear crosstalk due to optical add drop multiplexer and nonlinear crosstalk due to four wave mixing. Packet error rate analysis is chosen because it indicates how many IP packets are transmitted in error. The results show that a higher PER occurs in a WDM ring network when the number of nodes, the number of channels and the bit rate are higher. Increasing the burstiness of IP traffic improves the PER performance and allow more channels and larger number of nodes to be accommodated.